Campaña de comunicación integral por lanzamiento de avena instantánea Oh Tasty! - Salazar Masse, Monica Daniela (2021)
The major German transnational company Feldmeier & Co, leader in the food industry, will enter to compete in the Peruvian market, specifically in the market of cereals and oats, with the product of instant oats. The following work consists of the realization of a comprehensive marketing campaign to make known Oh Tasty!, the new brand of instant oatmeal. After the research and due to the pandemic context, it was decided to give more strength to the digital media, especially to the social media Instagram, which is where the largest number of people belonging to our target audience are concentrated. Using the concept "Your Ally in the mornings", the communication strategy aims to communicate the launch of the brand by highlighting its differential benefits such as its nutritional power, being a combination of Peruvian oats, quinoa and kiwicha, the fact that it is a healthy product as it does not contain artificial flavorings or preservatives, and its ease of preparation as it is a simple and quick product. It also seeks to break with the insight that instant food is always harmful to health and/or less nutritious than traditionally prepared food.